An at Glance Insight to Gut Microbiome Driven Autoimmunity - Shnawa, Ibrahim M S (British Journal of Healthcare and Medical Research, 2025)
Autoimmunity is attributed to genetic predisposition [Genome] and environmental factors[exposome] and microbiome[microbiota]. The objective of the present opinion paper was to present an at glance insight to gut microbiome driven autoimmune diseases GMDADs based upon current published literature .The exposome components are; infection ,vaccination ,allergy and stress .Human balanced microbiome is noted in immune homeostasis. While, in its dysbiotic state in which specific microbe linked to induction of auto immune reactions, the infectome. On the onset of autoimmune diseases, leaky gut initiated, the antigens of the infectious agent translocated, molecular mimicry, autoantigen overproduction and cytokine overproduction, all of these were moved through blood to other extra-intestinal compartments into which brook of tolerance and dysregulate homeostasis. Then, changes happened in transcription and translation of the gene(s) encoding the autoimmune reaction pathway along with the coevolved changes immune reaction pathways. To this end autoimmune reactions are either goes on or blocked by the dysbiotic microbiome. In case of rise up of autoimmune reactions producing clinical concentration levels of either auto –antibodies or auto-reactive T or B lymphocytes indicating autoimmune diseases. Auto-immune T cells produced in the gut lymphoid tissues migrate from gut to an eye auva leading to auto-immune auvitis. Gut lymphoid tissue produced T reg., migrate to reach the autoimmune inflamed central nervous system leading to inhibition of auto immune reactions. A suggestion for an animal model for infection induced auto immune disease in lapin animal was made. Not all dysbiotic microbiomes driven autoimmune diseases showing clear immunopathological mechanisms. A call suggestion for study the molecular mechanisms of the presently unknown microbiome driven autoimmune diseases.